IL-6 levels do not cause insulin resistance in newly diagnosed type 2 diabetic Sudanese patients - Mohamed Abdelrahim Ahmed; Ogail Yousif Dawod; Amar Babikir Elhussein; Abdulrahman A. Alsayegh; Husham E. Homeida; Hind Ali Osman; Solima I Yagoob; Monami Mukherjee Mondal; Ibrahim Ismail Mohammed Abu; Nahid Mahmoud Hassan Elamin (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective:Insulin resistance is a key feature of type 2 diabetes, characterized by the body's reduced ability to respond to the action ofthe hormone insulin. The exact mechanism behind the development of type II diabetes mellitus is not fully understood, although risk factors like obesity, inflammation, aging, and genetics are acknowledged. This study seeks to evaluate the association between IL6, an inflammatory mediator, and the onset of insulin resistance. Understanding this relationship could enhance our comprehension of the pathogenesis of type II diabetes mellitus and aid in advancing treatment and prevention strategies. Methods:The study comprised 115 recently diagnosed diabetic patients and 65 non-diabetic controls selected at random. Fasting blood samples were taken to measure plasma levels of IL-6, fasting insulin, and fasting plasma glucose. Subsequently, the homeostasis model assessment (HOMA-IR) was calculated to evaluate insulin resistance. Hierarchical regression analysis explored the relationship between IL-6 and insulin resistance. Additionally, all participants had their weight and height measured to calculate their Body Mass Index (BMI), which classified them into underweight, normal weight, overweight, and obese categories, while their age was noted for age subgroup classification. Results:The mean plasma concentrations of FBS, fasting insulin, and IL-6 were significantly higher in newly diagnosed diabetics (195.4 ± 59.0, 19.7 ± 6.,2 and 18.0 ± 12.7 respectively) compared to controls (82.3 ± 7.3, 9.5 ± 2.4 and 4.4 ± 2.4 respectively) (P ˂ 0.001 for all parameters) irrespective to their gender and BMI group. The overall hierarchical regression model including gender, log age, log BMI, and log IL-6 concentration was statistically significant (P = 0.003) with adjusted R2 = 0.065. IL6 showed a significant positive correlation with fasting blood glucose ((β= 0.209) (P value =0.005). Conversely, its correlation with plasma fasting insulin and insulin resistance was insignificantβ= 0.003 and β= 0.078, and the P value was 0.965 and 0.305 respectively for fasting insulin and insulin resistance. Conclusion:IL6 has not been associated with insulin resistance in newly diagnosed type 2 diabetic patients from Sudan.